Single photon double ionization of the helium dimer - Havermeier, Tilo; Jahnke, T.; Kreidi, K.; Wallauer, R.; Voss, S.; Schöffler, M.; Schössler, S.; Foucar, L.; Neumann, N.; Titze, J.; Sann, H.; Kühnel, M.; et al. (Physical review letters, 2010)
We show that a single photon can ionize the two helium atoms of the helium dimer in a distance up to 10 Å. The energy sharing among the electrons, the angular distributions of the ions and electrons, as well as comparison with electron impact data for helium atoms suggest a knockoff type double ionization process. The Coulomb explosion imaging of He2 provides a direct view of the nuclear wave function of this by far most extended and most diffuse of all naturally existing molecules.